Preparation method of polymethyl methacrylate / hydroxyapatite with lasting antibacterial function

By depositing unsaturated quaternary ammonium cations of silver bisphosphonate or copper bisphosphonate on the surface of nano-hydroxyapatite and copolymerizing them with methyl methacrylate, polymethyl methacrylate/hydroxyapatite composite materials were prepared. This solved the problems of insufficient osteogenicity, interfacial bonding strength and antibacterial function of PMMA-based bone cement, and achieved a comprehensive improvement effect of high strength, low heat and long-lasting antibacterial properties.

CN121021776APending Publication Date: 2025-11-28JIANGSU OCEAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511120546.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-12
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing PMMA-based bone cements have problems such as insufficient osteogenic properties, weak interfacial bonding, insufficient antibacterial function, high heat during polymerization and curing, and poor biocompatibility in bone repair or transplantation. Moreover, the modification effect is singular and it is difficult to achieve multiple modification effects simultaneously.

Method used

Polymerizable antibacterial hydroxyapatite is prepared by depositing unsaturated quaternary ammonium cations of silver bisphosphonate or copper bisphosphonate on the surface of nano-hydroxyapatite. This polymerizable antibacterial hydroxyapatite is then copolymerized with methyl methacrylate to form a polymethyl methacrylate/hydroxyapatite composite material. The two phases are connected by chemical bonds to achieve high bonding strength and dispersion, and the slow-release of silver or copper ions provides long-lasting antibacterial function.

Benefits of technology

It improves the flexural and compressive strength of PMMA-based bone cement, reduces curing heat and shrinkage, enhances biocompatibility, and provides long-lasting antibacterial effects, thus improving the overall performance of PMMA-based bone cement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0005542736420000041
    Figure BDA0005542736420000041
  • Figure BDA0005542736420000061
    Figure BDA0005542736420000061
Patent Text Reader

Abstract

The invention provides a preparation method of polymethyl methacrylate / hydroxyapatite with a lasting antibacterial function, which means that silver bisphosphonate containing unsaturated quaternary ammonium cations or copper bisphosphonate containing unsaturated quaternary ammonium cations is deposited on the surface of hydroxyapatite to prepare antibacterial hydroxyapatite with polymerization reaction characteristics. And the polymethyl methacrylate participates in a polymerization reaction of methyl methacrylate to prepare composite material micro powder with the hydroxyapatite surface grafted with polymethyl methacrylate. The polymethyl methacrylate / hydroxyapatite composite material micro powder has antibacterial and bacteriostatic performance, medical efficacy of diphosphonate, water absorption performance in a medium and biocompatibility performance, and can improve the binding force and dispersity of hydroxyapatite and polymethyl methacrylate; further, the tensile strength, the bending strength and the compressive strength of the polymethyl methacrylate-based bone cement are improved; the addition amount of hydroxyapatite in the polymethyl methacrylate-based bone cement is increased, so that the curing thermal effect and the curing shrinkage of the polymethyl methacrylate-based bone cement are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the preparation of multifunctional polymethyl methacrylate / hydroxyapatite composite material, in particular to the deposition of silver bisphosphonate with unsaturated quaternary ammonium cation in the molecular structure or copper bisphosphonate with unsaturated quaternary ammonium cation in the molecular structure on the surface of hydroxyapatite, followed by copolymerization with methyl methacrylate, to prepare polymethyl methacrylate / hydroxyapatite composite material with long-lasting antibacterial function, belonging to the field of medical functional materials. TECHNICAL BACKGROUND

[0002] Polymethyl methacrylate (PMMA) based bone cement is the main variety of bone adhesive used in bone graft or bone repair surgery. After decades of research and development, clinical application and effect observation, it is found that the major defect of PMMA based bone cement is its lack of osteogenic activity, which does not fuse with autologous bone in the long term. For many years, people have found that it has positive significance to compound inorganic powder materials such as hydroxyapatite micro powder, bioactive glass micro powder, or nano hydroxyapatite in PMMA based bone cement to form composite materials in order to improve the osteogenic activity of PMMA based bone cement. However, the interfacial bonding force of the above-mentioned composite materials is relatively small, and the dispersion of the inorganic powder materials in PMMA bone cement is also not easy to solve. Therefore, many documents have reported that the surface of hydroxyapatite or bioactive glass is modified by using amino silane coupling agent, vinyl silane coupling agent, isocyanate silane coupling agent, fatty acid, organic phosphonic acid and other small organic molecules, or after that, the modified hydroxyapatite or modified bioactive glass is grafted and polymerized on the surface, and the effect of improving the interfacial bonding force and dispersion of the composite material is remarkable. Another problem is that the antibacterial function of PMMA based bone cement in bone repair or transplantation is insufficient. In order to obtain PMMA based bone cement with antibacterial function, various methods and technologies have appeared in succession, such as using silver mirror reaction to plate silver on the surface of PMMA micro powder, or mixing with antibacterial polymers, antibiotics, and nano copper to make antibacterial PMMA composite micro powder. From the antibacterial effect, the addition of inorganic nano metal, antibacterial polymer or small molecule antibiotic can not achieve the expected effect. On the one hand, the added antibacterial agent may not be distributed on the surface of PMMA based bone cement, and the antibacterial agent distributed in the interior of PMMA based bone cement cannot be released or released slowly, which cannot achieve the antibacterial purpose; secondly, the addition of water-soluble antibacterial agent can be quickly dissolved and released in the body fluid, which can only ensure the early antibacterial effect, and lacks the ability to resist the continuous growth of bacteria for a long time. In addition, it is also found that PMMA based bone cement also has the following deficiencies: the mechanical strength (elastic modulus, bending strength, compressive strength, etc.) of PMMA bone cement after polymerization and curing does not match the autologous bone; the heat release during the polymerization and curing process of PMMA based bone cement is large, which causes the temperature of the surrounding human bone tissue or bone cells to be too high and necrosis; the MMA monomer residue during the polymerization and curing process of PMMA bone cement has biological toxicity; the volume shrinkage of PMMA based bone cement before and after polymerization and curing is obvious.People have also proposed solutions and techniques to solve the above problems, such as adding cellulose, carbon nanotubes, graphene oxide, nano-ZrO2, chitosan, sodium hyaluronate, polycaprolactone, polylactic acid, etc. in PMMA micro powder, and adding hydroxyapatite or bioactive glass, etc. The purpose is to improve the bending strength, compressive strength of PMMA-based bone cement, reduce the elastic modulus, reduce the curing heat, reduce the shrinkage of the cured body, and improve the biocompatibility, etc. All of them show some single aspect modification effect.

[0003] The professional people are familiar with PMMA-based bone cement has two components of powder / liquid, the main component in the powder is PMMA micro powder, and PMMA micro powder accounts for 52-89% of the mass fraction of PMMA-based bone cement powder, so the modification of PMMA micro powder naturally becomes the focus of attention. Another common PMMA micro powder modification is a high polymer material prepared by emulsion polymerization, suspension polymerization, dispersion polymerization or precipitation polymerization of monomer methyl methacrylate (abbreviated as MMA), so adding functional comonomer in the polymerization system of MMA can obtain PMMA copolymer micro powder, which can simply realize the optimization modification of PMMA-based bone cement. The functional monomers disclosed so far include acrylic acid, butyl methacrylate, hydroxyethyl methacrylate, vinyl pyrrolidone, methacryloyloxyethyl dimethyl benzyl ammonium chloride, 3,4-dichloro-5-hydroxy-5H-furan-2-ketone methacrylate, dimethylamino triclosan methacrylate, allyl isoniazid, etc. The purpose is to obtain copolymer PMMA with persistent hydrophilic, antibacterial properties, change the condensed state appearance of PMMA bone cement after curing, improve the bending strength, compressive strength, biocompatibility of PMMA-based bone cement, reduce the elastic modulus, curing heat and shrinkage of the cured body, etc. In summary, compounding or copolymerization is an effective method and means to endow PMMA with various functions, but there are few reports on a single modification that takes into account multiple modification effects and can obtain more optimized application performance.

[0004] Based on the performance, function and use requirement of PMMA micro powder material in PMMA base bone cement, aiming at the defects and deficiencies of existing modified hydroxyapatite / PMMA composite material, guaranteeing the safe and stable applicability of PMMA base bone cement, according to the chemical principle of molecular design, the present application creates the silver bisphosphonate or copper bisphosphonate with unsaturated quaternary ammonium cation deposited on the surface of nano hydroxyapatite, and prepares a modified hydroxyapatite with polymerizable reaction characteristics and durable antibacterial function, which is called polymerizable antibacterial hydroxyapatite for short; then through the copolymerization reaction of the polymerizable antibacterial hydroxyapatite and MMA, a composite material with poly (methyl methacrylate) chain grafted on the surface of antibacterial hydroxyapatite is prepared, which is used as PMMA micro powder in PMMA base bone cement. The two phases in the prepared poly (methyl methacrylate) / hydroxyapatite composite material are connected by chemical bonds, the binding force between PMMA and hydroxyapatite is high, and the dispersity is high; meanwhile, the composite material has osteogenic activity, bisphosphonate medical efficacy, water absorption performance in medium, biological affinity performance, and can significantly improve the bending strength and compressive strength of PMMA base bone cement, reduce the curing heat effect, curing body shrinkage and elastic modulus of PMMA base bone cement; most importantly, the water-insoluble characteristics of silver bisphosphonate or copper bisphosphonate cause the slow release of silver ions or copper ions of multifunctional PMMA micro powder, and the quaternary ammonium cation cooperates to produce durable antibacterial and bacteriostatic efficacy. SUMMARY

[0005] The hydroxyapatite with silver bisphosphonate or the hydroxyapatite with copper bisphosphonate deposited on the surface of the molecule structure and containing unsaturated quaternary ammonium cation, which is called polymerizable antibacterial hydroxyapatite for short, is copolymerized with methyl methacrylate to prepare a poly (methyl methacrylate) / hydroxyapatite composite material with durable antibacterial function, which is realized by the following steps: the solvent, dispersant, polymerizable antibacterial hydroxyapatite, methyl methacrylate and initiator are weighed and sent into a reaction kettle in sequence, stirred and dissolved or dispersed uniformly, and deoxygenated by nitrogen for half an hour, and then stirred and reacted at a temperature of 50-60 DEG C for 4-12 hours, the temperature of the material in the reaction kettle is increased to 70-90 DEG C for continuous stirring and reaction for 2 hours, and then the temperature of the material in the reaction kettle is reduced to room temperature, and the poly (methyl methacrylate) / hydroxyapatite is prepared through separation, washing and drying.

[0006] The mass ratio of methyl methacrylate, polymerizable antibacterial hydroxyapatite, initiator, dispersant and solvent is 100:5-150:1.5-15:5-30-200-2000.

[0007] The initiator refers to one or more of azobisisobutyronitrile, azobisisoheptyl nitrile, dimethyl azobisisobutyrate, benzoyl peroxide, lauroyl peroxide, lauroyl peroxide, azobisisobutyramidine hydrochloride, azobisisobutylimidazole hydrochloride, phenyl (2, 4, 6-trimethylbenzoyl) lithium phosphate, 4-isobutylphenyl-4'-methylphenyl iodine hexafluorophosphate, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy) phenyl]-1-propanone, or 2-hydroxy-2-methyl-1-phenyl-1-propanone.

[0008] The solvent refers to one or more of water, methanol, ethanol, propanol, butanol, tetrahydrofuran, 1, 4-dioxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, dimethyl sulfoxide, N-methyl pyrrolidone, N, N-dimethylformamide, N, N-diethylformamide, or hexamethylphosphoramide.

[0009] The dispersant refers to one or more of ethylene pyrrolidone, polyvinyl alcohol-1788, polyvinyl alcohol-2488, polyethylene glycol-2000, polyethylene glycol-4000, polyethylene glycol-6000, Span-80, Tween-80.

[0010] The polymerizable antibacterial hydroxyapatite is prepared by the following method:

[0011] Step one, preparation of antibacterial hydroxyapatite

[0012] A calcium salt aqueous solution with a molar concentration of 0.10-1.00 mol / L is added to a reaction kettle, and a phosphate salt solution prepared from an alcohol aqueous solution, an anti-caking agent, and a phosphate salt as raw materials is slowly added to the reaction kettle at room temperature under rapid stirring, and an appropriate amount of an alkali aqueous solution is used to adjust the pH of the materials in the reaction kettle to 7.5-10.5, and after reaction for 2-6 hours, a bisphosphonate aqueous solution with a mass percentage concentration of 30-300% containing a tertiary amine group is added to the reaction kettle, and finally a silver salt aqueous solution with a mass percentage concentration of 10-60% or a copper salt aqueous solution with a mass percentage concentration of 30-60% is added to the reaction kettle, and the temperature of the materials in the reaction kettle is controlled at 20-160℃, and the stirring is continued for 2-6 hours, and after cooling, the product is separated, washed, and dried to obtain the antibacterial hydroxyapatite.

[0013] The molar concentration of the phosphate salt in the phosphate salt solution is 0.10-1.00 mol / L, the amount of the phosphate salt solution is 30-300% of the volume of the calcium salt aqueous solution, the phosphate salt refers to one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, dipotassium hydrogen phosphate, or potassium dihydrogen phosphate, and the mass ratio of the phosphate salt in the phosphate salt solution / anti-caking agent / alcohol aqueous solution is 100:3-30:200-2000.

[0014] The calcium salt refers to one of calcium nitrate, calcium chloride, or calcium acetate.

[0015] The anti-caking agent refers to one or more of the following: polyvinylpyrrolidone, polyvinyl alcohol-1788, polyvinyl alcohol-2488, polyethylene glycol-2000, polyethylene glycol-4000, polyethylene glycol-6000, Span-80, Tween-80, N-dodecyl-N,N,N-trimethylammonium bromide, N-tetradecyl-N,N,N-trimethylammonium bromide, N-hexadecyl-N,N,N-triethylammonium bromide, N-dodecyl-N,N,N-triethylammonium bromide, N-tetradecyl-N,N,N-triethylammonium bromide, and N-hexadecyl-N,N,N-triethylammonium bromide.

[0016] The alkaline aqueous solution refers to either a sodium hydroxide aqueous solution or a potassium hydroxide aqueous solution with a mass percentage concentration of 10-30%.

[0017] The alcohol-water solution refers to a mixture of methanol, ethanol, or propanol and deionized water in a mass ratio of 5 to 50:100.

[0018] The bisphosphonate containing a tertiary amine group has the structure shown in general formula (Ⅰ):

[0019]

[0020] In general formula (Ⅰ), R1 and R1 are selected from C1 to C1 respectively. 18 hydrocarbon group, M + Select Na + or K + One of them; the amount of the tertiary amine-containing bisphosphonate used is 5 to 150% of the mass of the phosphate.

[0021] The silver salt aqueous solution refers to a silver nitrate aqueous solution with a pH value of 5.0 to 6.5, and the amount of silver nitrate used is 0.1 to 2.0 times the molar amount of bisphosphonate containing tertiary amine groups; or the copper salt aqueous solution refers to a copper sulfate aqueous solution with a pH value of 5.0 to 6.5, and the amount of copper sulfate used is 0.1 to 2.0 times the molar amount of bisphosphonate containing tertiary amine groups.

[0022] Step 2: Preparation of polymerizable antibacterial hydroxyapatite

[0023] Organic solvent, polymerization inhibitor and antibacterial hydroxyapatite obtained in step one are weighed in sequence and added to a reaction vessel. After nitrogen purging and deoxygenation, unsaturated halogenated hydrocarbons are added to the reaction vessel. The temperature of the material in the reaction vessel is raised to 40-120°C. After stirring and reacting for 6-60 hours, the temperature of the material in the reaction vessel is lowered to room temperature. After separation, washing and drying, polymerizable antibacterial hydroxyapatite is obtained.

[0024] The mass ratio of the antibacterial hydroxyapatite / unsaturated halogenated hydrocarbon / polymerization inhibitor / organic solvent is 100:5-150:0.15-15:50-1000.

[0025] The unsaturated halogenated hydrocarbon refers to one of 3-chloropropene, 3-bromopropene, or p-chloromethylstyrene.

[0026] The polymerization inhibitor refers to one or two or more of hydroquinone, p-methoxyphenol, t-butyl hydroquinone, 2,6-dibutyl hydroquinone, 2,6-di-t-butyl-p-cresol, or 2,4,6-tri-t-butylphenol.

[0027] The organic solvent refers to one or two or more of tetrahydrofuran, 1,4-dioxane, cyclohexane, decalin, benzene, toluene, chlorobenzene, dichloromethane, chloroform, carbon tetrachloride, acetonitrile, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, or N,N-dimethylacetamide.

[0028] The professional personnel can know that the tertiary amine group-containing bisphosphonate salt in the application can be adsorbed on the surface of hydroxyapatite by Ca-O-P bond, and can also react with silver salt or copper salt to uniformly form a tertiary amine group-containing bisphosphonate silver or a tertiary amine group-containing bisphosphonate copper deposited on the surface of hydroxyapatite, thereby forming a eutectic composite of the tertiary amine group-containing bisphosphonate silver or the tertiary amine group-containing bisphosphonate copper surface-deposited hydroxyapatite, which is called antibacterial hydroxyapatite. The hydroxyapatite obtained in the application has the characteristics of nucleophilic substitution reaction with unsaturated halogenated hydrocarbons after the surface deposition of the tertiary amine group-containing bisphosphonate silver or the tertiary amine group-containing bisphosphonate copper, so the antibacterial hydroxyapatite further undergoes quaternary ammonium saltization reaction with the quaternary ammonium salt of unsaturated halogenated hydrocarbons in an organic solvent, thereby obtaining the hydroxyapatite with polymerization reaction characteristics and antibacterial function in the application, which is simply called polymerizable antibacterial hydroxyapatite. The polymerizable antibacterial hydroxyapatite participates in the MMA polymerization reaction to obtain a polymethyl methacrylate / hydroxyapatite composite material, which is simply called PMMA / HA. The professional personnel can see that the polymeric state structure of the polymethyl methacrylate / hydroxyapatite composite material has the structure units or chemical substances of the polymeric methyl methacrylate chain, the side chain connected with the quaternary ammonium cation, the chemical grafting (bisphosphonate silver / bisphosphonate copper + hydroxyapatite) of the polymeric methyl methacrylate chain, and the high-free hydrocarbon group which can creep when heated, wherein the hydroxyapatite and the PMMA polymer are combined by chemical bonds, so the combination force between the organic / inorganic two phases is strong, the dispersivity of the hydroxyapatite in the PMMA polymer is high, the hydroxyapatite does not agglomerate, and the tensile strength, the bending strength and the compressive strength of the PMMA-based bone cement can be improved, and the addition amount of the hydroxyapatite in the PMMA-based bone cement can be increased, thereby reducing the curing heat effect and the curing body shrinkage of the PMMA-based bone cement. At the same time, the multifunctional PMMA has the antibacterial and bacteriostatic functions of silver ion or copper ion release, the medical functions of bisphosphonate, the water absorption performance in the medium, the osteogenic property and the biological affinity performance. DETAILED DESCRIPTION

[0029] In order to further understand the application, the application will be specifically described by way of examples, and the purpose is to better understand the content of the application. Therefore, the polymerizable antibacterial hydroxyapatite (1) in the examples should not be regarded as a limitation on the protection scope of the application.

[0030] Example 1 Preparation of polymerizable antibacterial hydroxyapatite (1)

[0031] Step one, preparation of antibacterial hydroxyapatite (1)

[0032] In a reaction kettle, first add 220 grams of calcium nitrate aqueous solution with a molar concentration of 0.52 mol / L, then successively weigh 30 grams of ethanol, 70 grams of deionized water, 1.2 grams of polyvinyl alcohol-1788, and 10.5 grams of ammonium dihydrogen phosphate to prepare a phosphate aqueous solution, slowly add the phosphate aqueous solution to the reaction kettle at room temperature under rapid stirring, use an appropriate amount of 15% mass percent caustic aqueous solution to adjust the pH of the material in the reaction kettle to be greater than or equal to 9.0, after 2 hours of reaction, add 50 grams of an aqueous solution containing 15.4 grams of sodium bisphosphonate of formula (I-1) containing a tertiary amine group to the reaction kettle, stir uniformly, then add 45 grams of an aqueous silver nitrate solution containing 8.3 grams of silver nitrate, control the temperature to be 100-120°C, stir for 4 hours of reaction, then cool and age for 24 hours, centrifuge, wash several times with an ethanol aqueous solution with a volume ratio of 1:1, then send to a vacuum drying oven, control the temperature to be 50-60°C, and vacuum dry to obtain 32.03 grams of antibacterial hydroxyapatite (1). The SEM shows that the antibacterial hydroxyapatite (1) is a rod columnar nanometer powder with a particle size of 43-150 nm. TGA analysis shows that the antibacterial hydroxyapatite (1) has a thermal weight loss of about 6.76% between 20-200°C, which should be attributed to the loss of crystal water; the thermal weight loss is about 33.72% between 200-450°C, which should be attributed to the thermal decomposition loss of the organic components in the antibacterial hydroxyapatite (1), which is consistent with the proportion of the raw material formula used to prepare the antibacterial hydroxyapatite (1). The antibacterial hydroxyapatite (1) has almost no thermal weight loss between 450-700°C. Compared with pure hydroxyapatite, the IR (KBr pressed tablet, cm -1 ) of the antibacterial hydroxyapatite (1) has new characteristic absorption peaks at 2934, 2876, and 1544, which should correspond to methyl, methylene, and C-N, respectively, thereby confirming that the antibacterial hydroxyapatite (1) is a hydroxyapatite surface deposited with silver bisphosphonate nanometer powder containing a tertiary amine group.

[0033] The following reaction formula represents the preparation method and process of the sodium bisphosphonate of formula (I-1) containing a tertiary amine group:

[0034]

[0035] 30 g of N,N-dimethyl-1,3-propanediamine and 80 g of anhydrous ethanol were added to a reactor. The temperature of the material in the reactor was controlled at 20–25 °C. 56 g of diethyl vinylphosphonate was slowly added. After the addition of diethyl vinylphosphonate was completed, the temperature of the material in the reactor was raised to 50–60 °C and stirred for 12 hours. After rotary evaporation to recover ethanol and excess diethyl vinylphosphonate, 5.5 mol / L hydrochloric acid was added to the reactor until the residue in the reactor was completely dissolved. The temperature was controlled at 90–100 °C and stirred for 24 hours for hydrolysis. The temperature of the hydrolysis product was lowered to room temperature. The pH of the material in the reactor was adjusted to 11 using a 30% sodium hydroxide aqueous solution. The mixture was concentrated by rotary evaporation until solid substances precipitated. The mixture was then cooled and allowed to stand to precipitate solid products. After filtration, recrystallization with 93% aqueous ethanol, and vacuum drying at 40–50 °C to constant weight, 103.8 g of white powder product with a melting range of 133–136 °C was obtained. Elemental analysis (%) of the white powdery product: C 29.32, H 6.03, N 7.71, P 17.18, similar to C9H 22 The calculated values ​​of N2P2O6Na2 (C 29.84, H 6.12, N 7.73, P 17.10) are basically consistent; its IR (KBr tablet, cm⁻¹) is also consistent. -1 The values ​​3433, 2934, 2872, 1445, 1360, 1262, 1108, 964, and 926 are attributed to the characteristic vibrational absorption peaks of H2O, CH3, CH2, CN, P=O, and PO, respectively. 1 ¹H-NMR (TMS as internal standard, D₂O, δ): 1.43 (t, 4H), 1.59 (m, 2H), 2.24 (s, 6H), 2.37 (t, 4H), 2.48 (t, 4H). Based on elemental analysis, IR and... 1 The 1H-NMR spectral analysis confirmed that the white powdery product has the structural features shown in formula (Ⅰ-1).

[0036] Step 2: Preparation of polymerizable antibacterial hydroxyapatite (1)

[0037] Example 2 Preparation of polymerizable antibacterial hydroxyapatite (2)

[0038] The above results show that 2.17 g of 3-bromo-propene reacted with antibacterial hydroxyapatite (1), which is equivalent to 0.01808 moles of bromo-propene to achieve quaternary ammonium salt reaction. The original antibacterial hydroxyapatite (1) contains 0.0219 moles of tertiary amine groups, so the quaternary ammonium salt reaction efficiency of 3-bromo-propene with antibacterial hydroxyapatite (1) is 0.01808 / 0.0219 = 82.6%. The results show that both of the two tertiary amine groups in antibacterial hydroxyapatite (1) have undergone quaternary ammonium salt reaction to different degrees. The SEM of polymerizable antibacterial hydroxyapatite (1) shows that the particle size is 55-156 nm, indicating that the particle size of polymerizable antibacterial hydroxyapatite (1) after quaternary ammonium salt reaction has not changed significantly compared with antibacterial hydroxyapatite (1).

[0039] Example 2 Preparation of polymerizable antibacterial hydroxyapatite (2)

[0040] According to the methods and steps of the example, the sodium bisphosphonate with tertiary amine group in step one of Example 1 is replaced by sodium bisphosphonate with tertiary amine group of formula (I-2):

[0041]

[0042] The antibacterial hydroxyapatite (2) powder with a particle size of 40-228 nm was prepared; the 3-bromopropylene in step two of Example 1 was replaced by p-chloromethylstyrene, and the quaternary ammonium salt reaction was carried out on the antibacterial hydroxyapatite (2) to prepare the polymerizable antibacterial hydroxyapatite (2) powder with a particle size of 53-300 nm. Through analysis and comparison, the result shows that the quaternary ammonium salt reaction efficiency of the two tertiary amine groups on the polymerizable antibacterial hydroxyapatite (2) is about 67.4%.

[0043] Preparation of polymerizable antibacterial hydroxyapatite (3) in Example 3

[0044] The silver nitrate in step one of Example 1 was replaced by copper sulfate according to the method and steps of Example 1 to prepare the antibacterial hydroxyapatite (3) powder with a particle size of 52-165 nm; the quaternary ammonium salt reaction was carried out on the antibacterial hydroxyapatite (3) and 3-bromopropylene to prepare the polymerizable antibacterial hydroxyapatite (3) powder with a particle size of 53-165 nm. Through analysis and comparison, the result shows that the quaternary ammonium salt reaction efficiency of the two tertiary amine groups on the polymerizable antibacterial hydroxyapatite (3) is about 77.4%.

[0045] Preparation of polymerizable antibacterial hydroxyapatite (4) in Example 4

[0046] The silver nitrate in step one of Example 1 was replaced by copper sulfate according to the method and steps of Example 1 to prepare the antibacterial hydroxyapatite (4) powder with a particle size of 52-165 nm; the quaternary ammonium salt reaction was carried out on the antibacterial hydroxyapatite (4) and 3-bromopropylene to prepare the polymerizable antibacterial hydroxyapatite (4) powder with a particle size of 56-185 nm. Through analysis and comparison, the result shows that the quaternary ammonium salt reaction efficiency of the two tertiary amine groups on the polymerizable antibacterial hydroxyapatite (4) is about 64.6%.

[0047] From the preparation of the antibacterial hydroxyapatite in Example 1, 2, 3 and 4, it can be seen that the silver bisphosphonate containing tertiary amine groups or the copper bisphosphonate containing tertiary amine groups is deposited on the surface of the hydroxyapatite. Because the tertiary amine groups of the silver bisphosphonate containing tertiary amine groups or the copper bisphosphonate containing tertiary amine groups deposited on the surface of the hydroxyapatite are mostly distributed on the surface layer of the hydroxyapatite powder, it is easy to carry out the quaternary ammonium salt reaction with the unsaturated halogenated hydrocarbon. In addition, the particle size of the hydroxyapatite powder material before and after the quaternary ammonium salt reaction does not change obviously.

[0048] Preparation of polymethyl methacrylate / hydroxyapatite (1) in Example 5

[0049] A mixed solution consisting of 93 g of ethanol, 7 g of deionized water, and 1.3 g of polyvinylpyrrolidone K-30 was added to a reaction vessel. Then, 12 g of methyl methacrylate, 8 g of polymerizable antibacterial hydroxyapatite (1), and 0.38 g of azobisisobutyronitrile were weighed and mixed together. After ultrasonic treatment at room temperature for 1 hour, the mixture was added to the reaction vessel, stirred and dispersed evenly, and nitrogen was purged for half an hour to remove oxygen. The temperature was controlled at 50-60℃ and stirred for 8 hours. Then, the temperature of the material in the reaction vessel was increased to 70-90℃ and stirred for another 2 hours. The temperature in the reaction vessel was then reduced to room temperature. After filtration, washing with ethanol, and vacuum drying at 50-60℃, 21.5 g of micronized polymethyl methacrylate / hydroxyapatite (1) was obtained. SEM analysis of polymethyl methacrylate / hydroxyapatite (1) showed a particle size of 1.2–15.5 μm. TGA analysis showed that polymethyl methacrylate / hydroxyapatite (1) lost about 1.61% of its weight between 20 and 200 °C, which was attributed to the loss of its water of crystallization. Between 200 and 450 °C, it lost about 62.8% of its weight, which should be attributed to the thermal decomposition loss of the organic components in polymethyl methacrylate / hydroxyapatite (1). There was no further weight loss up to 700 °C.

[0050] Example 6 Preparation of polymethyl methacrylate / hydroxyapatite (2)

[0051] Weigh 12g of methyl methacrylate, 8g of polymerizable antibacterial hydroxyapatite (2) and 1.5g of azobisisobutyronitrile (AIBN), mix them together, sonicate at room temperature for 1 hour and then put them into a reaction vessel. Then add a mixed solution consisting of 93g of ethanol, 7g of deionized water and 2.1g of polyvinylpyrrolidone K-30, stir and disperse evenly, and purge with nitrogen to remove oxygen for half an hour. Stir and react for 8 hours at a controlled temperature of 50-60℃. Then raise the temperature of the material in the reaction vessel to 70-90℃ and continue stirring and reacting for 2 hours. Lower the temperature in the reaction vessel to room temperature, filter, wash with ethanol, and vacuum dry at a controlled temperature of 50-60℃ to obtain 20.93g of micronized polymethyl methacrylate / hydroxyapatite (2). SEM analysis of polymethyl methacrylate / hydroxyapatite (2) showed a particle size of 1.4–14.5 μm. TGA analysis showed that polymethyl methacrylate / hydroxyapatite (2) lost about 1.43% of its weight between 20 and 200 °C, which was attributed to the loss of its water of crystallization. Between 200 and 450 °C, it lost about 65.11% of its weight, which should be attributed to the thermal decomposition loss of the organic components in polymethyl methacrylate / hydroxyapatite (2). There was no further weight loss up to 700 °C.

[0052] Example 7 Preparation of polymethyl methacrylate / hydroxyapatite (3)

[0053] Methyl methacrylate 8 grams, 12 grams of polymerizable antibacterial hydroxyapatite (2) and azobisisobutyronitrile 1.5 grams were mixed together, and after ultrasonic treatment at room temperature for 1 hour, they were put into a reaction kettle. Then a mixed solution composed of ethanol 93 grams, deionized water 7 grams, and 1.3 grams of polyvinylpyrrolidone K-30 was added, and stirred and dispersed uniformly. Nitrogen was filled to remove oxygen for half an hour, and the temperature was controlled at 50-60°C for stirring reaction for 8 hours. Then the temperature of the material in the reaction kettle was increased to 70-90°C for continued stirring reaction for 2 hours. The temperature in the reaction kettle was reduced to room temperature, and after filtration, ethanol washing, and vacuum drying at a temperature controlled at 50-60°C, 20.97 grams of micropowdered polymethyl methacrylate / hydroxyapatite (3) were prepared. The SEM of polymethyl methacrylate / hydroxyapatite (3) showed that the particle size was 1.5-14.3 μm; TGA analysis showed that the thermal weight loss of polymethyl methacrylate / hydroxyapatite (3) was about 1.71% between 20-200°C, which was attributed to the loss of crystal water; the thermal weight loss was about 56.58% between 200-450°C, which should be attributed to the thermal decomposition loss of the organic components in polymethyl methacrylate / hydroxyapatite (3); and there was no thermal weight loss up to 700°C.

[0054] Example 8 Preparation of polymethyl methacrylate / hydroxyapatite (4)

[0055] Methyl methacrylate 30 grams, 10 grams of polymerizable antibacterial hydroxyapatite (2) and azobisisobutyronitrile 1.8 grams were mixed together, and after ultrasonic treatment at room temperature for 1 hour, they were put into a reaction kettle. Then a mixed solution composed of ethanol 130 grams, deionized water 70 grams, and 1.8 grams of polyvinylpyrrolidone K-30 was added, and stirred and dispersed uniformly. Nitrogen was filled to remove oxygen for half an hour, and the temperature was controlled at 50-60°C for stirring reaction for 8 hours. Then the temperature of the material in the reaction kettle was increased to 70-90°C for continued stirring reaction for 2 hours. The temperature in the reaction kettle was reduced to room temperature, and after filtration, ethanol washing, and vacuum drying at a temperature controlled at 50-60°C, 30.12 grams of micropowdered polymethyl methacrylate / hydroxyapatite (4) were prepared. The SEM of polymethyl methacrylate / hydroxyapatite (4) showed that the particle size was 4.5-12.5 μm; TGA analysis showed that the thermal weight loss of polymethyl methacrylate / hydroxyapatite (4) was about 1.21% between 20-200°C, which was attributed to the loss of crystal water; the thermal weight loss was about 71.22% between 200-450°C, which should be attributed to the thermal decomposition loss of the organic components in polymethyl methacrylate / hydroxyapatite (4); and there was no thermal weight loss up to 700°C.

[0056] Example 9 Properties of modified hydroxyapatite and PMMA / HA micropowder

[0057] The antibacterial hydroxyapatite in Examples 1-4, the polymerizable hydroxyapatite 1.5 g, and the polymethyl methacrylate / hydroxyapatite micropowder in Examples 5-8 0.5 g were weighed respectively, and pressed into tablets by a tablet press. The pure water contact angle of each tablet was measured by a contact angle measuring instrument under static state. It was found that the water contact angle of the hydroxyapatite surface deposited with silver bisphosphonate containing tertiary amine group and copper bisphosphonate containing tertiary amine group was obviously increased, and was between 5.0-13.5°. The water contact angle of the antibacterial hydroxyapatite in Example 2 and Example 4 was greater than that in Example 1 and Example 3, indicating that the greater the volume of tertiary amine group, the greater the water contact angle of the antibacterial hydroxyapatite. The contact angle of the polymerizable hydroxyapatite in Examples 1-4 could not be measured. The reason was that the water droplet entered into the tablet instantly after contacting the tablet, indicating that the polymerizable hydroxyapatite in Examples 1-4 had water wettability. The water contact angle of the polymethyl methacrylate / hydroxyapatite micropowder tablet in Examples 5-8 was 37.3°, 38.4°, 21.3° and 55.5° respectively, indicating that the water contact angle of the hydroxyapatite surface grafted with PMMA in Examples 1-4 would be increased, and the higher the amount of PMMA grafted on the surface of the hydroxyapatite, the greater the water contact angle.

[0058] The method and operation steps specified in GBT 21510-2008 "Nano-inorganic antibacterial material antibacterial performance detection method" were referred to. 1.0000 g of the antibacterial hydroxyapatite and polymerizable hydroxyapatite in Examples 1-4, and the polymethyl methacrylate / hydroxyapatite micropowder in Examples 5-8 were weighed respectively, and added into 5.0 mL of a 1×10 6 CFU / mL S. aureus or E. coli bacterial suspension, and then added into 95 mL of a phosphate buffer containing 0.1% Tween-80. After oscillation culture in a 37°C constant temperature incubator for 2, 12 or 24 hours, the total number of the remaining living bacteria was counted, and the antibacterial performance of the modified hydroxyapatite and the polymethyl methacrylate / hydroxyapatite micropowder in Examples 5-8 was quantitatively evaluated. The results are shown in Tables 1 and 2.

[0059] Table 1 Antibacterial performance of modified hydroxyapatite

[0060]

[0061] Table 2 Antibacterial performance of PMMA / HA

[0062]

[0063] The results in Table 1 confirmed that the higher the density of quaternary ammonium cation on the surface of the polymerizable hydroxyapatite powder, the higher the antibacterial activity. The hydrocarbon group of the quaternary ammonium cation was changed from C3 hydrocarbon group to C7 or C 12The hydrocarbon group also has a significantly improved antibacterial activity. The results in Table 2 show that after grafting PMMA chains onto the antibacterial hydroxylapatite surface, the contact action of the hydroxylapatite in the water system with pathogenic bacteria is reduced, and the antibacterial effect is also reduced.

Claims

1. A method for preparing polymethyl methacrylate / hydroxyapatite with long-lasting antibacterial function, comprising the following steps: solvent, dispersant, polymerizable antibacterial hydroxyapatite, methyl methacrylate, and initiator are weighed sequentially into a reaction vessel according to a mass ratio of 200~2000:5~30:5~150:100:1.5~15, stirred to dissolve or disperse evenly, purged with nitrogen for half an hour to remove oxygen, and stirred at 50~60℃ for 4~12 hours. The temperature of the material in the reaction vessel is then increased to 70~90℃ and stirred for another 2 hours. The temperature in the reaction vessel is then reduced to room temperature. After separation, washing, and drying, polymethyl methacrylate / hydroxyapatite with long-lasting antibacterial function is obtained, characterized in that… The polymerizable antibacterial hydroxyapatite refers to silver bisphosphonate with unsaturated quaternary ammonium cations in its surface-deposited molecular structure, or copper bisphosphonate with unsaturated quaternary ammonium cations in its surface-deposited molecular structure.

2. The method for preparing a polymethyl methacrylate / hydroxyapatite with long-lasting antibacterial function according to claim 1, characterized in that... The dispersant refers to one or more of the following: vinylpyrrolidone, polyvinyl alcohol-1788, polyvinyl alcohol-2488, polyethylene glycol-2000, polyethylene glycol-4000, polyethylene glycol-6000, Span-80, and Tween-80.

3. The method for preparing polymethyl methacrylate / hydroxyapatite with long-lasting antibacterial function according to claim 1, characterized in that... The initiator refers to one or more of the following: azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, lauroyl peroxide, lauroyl peroxide, azobisisobutyramidine hydrochloride, azobisisobutyramidine imidazoline hydrochloride, lithium phenyl (2,4,6-trimethylbenzoyl)phosphate, 4-isobutylphenyl-4'-methylphenyliodohexafluorophosphate, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, or 2-hydroxy-2-methyl-1-phenyl-1-propanone.

4. The method for preparing polymethyl methacrylate / hydroxyapatite with long-lasting antibacterial function according to claim 1, characterized in that... The solvent refers to one or more of the following: water, methanol, ethanol, propanol, butanol, tetrahydrofuran, 1,4-dioxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide, N,N-diethylformamide, or hexamethylphosphoramide.

5. The method for preparing a polymethyl methacrylate / hydroxyapatite with long-lasting antibacterial function according to claim 1, characterized in that... The polymerizable antibacterial hydroxyapatite is prepared by the following method: Step 1: Preparation of antibacterial hydroxyapatite A calcium salt aqueous solution with a molar concentration of 0.10~1.00mol / L was added to a reaction vessel. Under rapid stirring, a phosphate solution prepared from alcohol aqueous solution, anti-caking agent, and phosphate was slowly added to the reaction vessel at room temperature. An appropriate amount of alkaline aqueous solution was used to adjust the pH of the material in the reaction vessel to between 7.5 and 10.

5. After reacting for 2~6 hours, a bisphosphonate aqueous solution containing tertiary amine groups with a mass percentage concentration of 30~300% was added to the reaction vessel. Finally, a silver salt aqueous solution with a mass percentage concentration of 10~60% or a copper salt aqueous solution with a mass percentage concentration of 30~60% was added to the reaction vessel. The temperature of the material in the reaction vessel was controlled between 20~160℃. The reaction was continued with stirring for 2~6 hours. After cooling, precipitation, separation, washing, and drying, antibacterial hydroxyapatite was obtained. The phosphate solution has a phosphate molar concentration of 0.10~1.00 mol / L, and the amount of phosphate solution used is 30~300% of the volume of the calcium salt aqueous solution. The phosphate refers to one or more of the following: ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, dipotassium hydrogen phosphate, or potassium dihydrogen phosphate. The mass ratio of phosphate / anti-caking agent / alcohol aqueous solution in the phosphate solution is 100:3~30:200~2000. The calcium salt refers to one of calcium nitrate, calcium chloride, or calcium acetate. The bisphosphonate containing a tertiary amine group has the structure shown in general formula (Ⅰ): ; In general formula (Ⅰ), R1 and R1 are selected from C1 to C1 respectively. 18 hydrocarbon group, M + Select Na + or K + One of them; the amount of the tertiary amine-containing bisphosphonate used is 5-150% of the mass of the phosphate; The silver salt aqueous solution refers to a silver nitrate aqueous solution with a pH value of 5.0 to 6.5, and the amount of silver nitrate used is 0.1 to 2.0 times the molar amount of bisphosphonate containing tertiary amine groups; or the copper salt aqueous solution refers to a copper sulfate aqueous solution with a pH value of 5.0 to 6.5, and the amount of copper sulfate used is 0.1 to 2.0 times the molar amount of bisphosphonate containing tertiary amine groups. Step 2: Preparation of polymerizable antibacterial hydroxyapatite According to the mass ratio of 50~1000:100:5~150:0.15~15, the organic solvent, the antibacterial hydroxyapatite obtained in step one, the unsaturated halogenated hydrocarbons, and the polymerization inhibitor were weighed in sequence and added to the reaction vessel. After nitrogen purging and deoxygenation, the temperature of the material in the reaction vessel was raised to 40~120℃. After stirring and reacting for 6~60 hours, the temperature of the material in the reaction vessel was lowered to room temperature. After separation, washing, and drying, polymerizable antibacterial hydroxyapatite was obtained. The unsaturated halohydrocarbons mentioned therein refer to one of 3-chloropropene, 3-bromopropene, or p-chloromethylstyrene.

6. The method for preparing a polymethyl methacrylate / hydroxyapatite with long-lasting antibacterial function according to claim 5, characterized in that... The anti-caking agent is selected from one or more of the following: polyvinylpyrrolidone, polyvinyl alcohol-1788, polyvinyl alcohol-2488, polyethylene glycol-2000, polyethylene glycol-4000, polyethylene glycol-6000, Span-80, Tween-80, N-dodecyl-N,N,N-trimethylammonium bromide, N-tetradecyl-N,N,N-trimethylammonium bromide, N-hexadecyl-N,N,N-triethylammonium bromide, N-dodecyl-N,N,N-triethylammonium bromide, N-tetradecyl-N,N,N-triethylammonium bromide, and N-hexadecyl-N,N,N-triethylammonium bromide.

7. The method for preparing a polymethyl methacrylate / hydroxyapatite with long-lasting antibacterial function according to claim 5, characterized in that... The alkaline aqueous solution refers to either a sodium hydroxide aqueous solution or a potassium hydroxide aqueous solution with a mass percentage concentration of 10-30%.

8. The method for preparing a polymethyl methacrylate / hydroxyapatite with long-lasting antibacterial function according to claim 5, characterized in that... The alcohol-water solution refers to a mixture of methanol, ethanol, or propanol and deionized water in a mass ratio of 5 to 50:

100.

9. A method for preparing a polymethyl methacrylate / hydroxyapatite with long-lasting antibacterial function according to claim 5, characterized in that... The polymerization inhibitor is selected from one or more of hydroquinone, p-methoxyphenol, tert-butylhydroquinone, 2,6-dibutylhydroquinone, 2,6-di-tert-butyl-p-cresol, or 2,4,6-tri-tert-butylphenol.

10. A method for preparing a polymethyl methacrylate / hydroxyapatite with long-lasting antibacterial function according to claim 5, characterized in that... The organic solvent is selected from one or more of tetrahydrofuran, 1,4-dioxane, cyclohexane, decahydronaphthalene, benzene, toluene, chlorobenzene, dichloromethane, chloroform, carbon tetrachloride, acetonitrile, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, or N,N-dimethylacetamide.